ENVIRONMENTAL DETERMINANTS OF MUSICAL CULTURE DEVELOPMENT AS REFLECTIVE INSTRUMENTS OF THE VISUAL TURN - Arefieva, Elizaveta (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The response to the challenges posed by technological innovations in cultural genesis is the emergence of a broad ecosystem movement in philosophical and cultural studies reflection. The context in which this reflection, especially in art criticism, finds itself increasingly relies on visual artifacts, and visuality substitutes for philosophy, with the image assuming the role of an ontological essence. The aim of the article is to define the phenomenon of the ecosystem approach to the interpretation of modern musical culture in the context of the visual turn. The research methodology is presented with comparative and polysystemic approaches, making it possible to analyze metacultural and meta-artistic integrity of musical culture as a certain synthesis of the reconstruction of the determinants of the human dimension of visual and virtual transformations of musical content. Research results. The visual turn is the latest innovation of cultural reflection, which is widely advertised and presented as a kind of communicative and at the same time spectacular constant of today’s culture. Ecological dimensions of cultural creation actualize the definition of increased reflectivity, areflexivity, escapism, and replacement of reality with a representation as a certain simulacrum, which sooner or later declares itself as a rejection of the human dimension of creativity, replacing it with a visual-virtual technocenosis of the musical cultural space. Discussion. The replacement of the artistic act with the realities of visuality, which acquire an extremely expressive, ecstatic and at the same time aggressive appearance, prompts what is said to be a visual turn when the visual status of the eidetic of musical content acquires the completed image of the musical space of culture. Conclusions. The horizons of the understanding of cultural values are changing, and new contexts for the presentation of cultural practices, in particular music, are being formed. A kind of art reality arises, which prompts certain hybrid art projects, such as visual design, television, video, media constellations, and art constructions, which are artistic creations, where music is translated into the language of the visual. On the one hand, a wide pressure of artification dominates, on the other, systems of cultural creation are being formed, which can be associated with the underground, a kind of cryptoculture, which is purely marginal and is formed in conditions of visual reservations.